The Application of Injection - Grouting for Strengthening of the Weak Subgrade Foundations (preprint) - Petrenko, Volodymyr D.; Sviatko, Ilona O.; Yampolskyy, D. O. (PGASA, 2014)
ENG: This article analyzes the features of the subgrade construction on soft soils, and offers to use injection–grouting technology, which is widely used abroad, but needs official regulations for the application in observed area.

UKR: В цій статті проаналізовано особливості спорудження земляного полотна на слабких ґрунтах, і пропонується використання методу струминної цементації, який широко застосовується за кордоном, але потребує рекомендацій щодо застосування.

RUS: В этой статье проанализированы особенности сооружения земляного полотна на слабых грунтах, и предлагается использование метода струйной цементации, который широко применяется за рубежом, но нуждается в рекомендациях по применению.
Використання струминної цементації для укріплення слабких основ земляного полотна (препринт)
Использования струйной цементации для укрепление слабого основания земляного полотна (препринт)
V. Petrenko: ORCID 0000-0002-5902-6155; I. Sviatko: ORCID 0000-0002-7099-2637; D. Yampolskyy: ORCID 0000-0003-7039-3633
Keywords: soft soils; soil massif; injection-grouting technology; слабкий ґрунт; ґрунтовий масив; метод струминної цементації; слабый грунт; грунтовый массив; метод струминной цементации; КТОФ